2017
DOI: 10.1111/nph.14679
|View full text |Cite
|
Sign up to set email alerts
|

MYB30 transcription factor regulates oxidative and heat stress responses through ANNEXIN‐mediated cytosolic calcium signaling in Arabidopsis

Abstract: Cytosolic calcium signaling is critical for regulating downstream responses in plants encountering unfavorable environmental conditions. In a genetic screen for Arabidopsis thaliana mutants defective in stress-induced cytosolic free Ca ([Ca ] ) elevations, we identified the R2R3-MYB transcription factor MYB30 as a regulator of [Ca ] in response to H O and heat stresses. Plants lacking MYB30 protein exhibited greater elevation of [Ca ] in response to oxidative and heat stimuli. Real-time reverse transcription-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
121
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 76 publications
3
121
0
Order By: Relevance
“…An annexin with a high T = 0 expression showed a strong transcript level rise at the higher water deficit (Cc10_g07300, FC = 2.5). Annexins have been linked to drought and oxidative responses, potentially via ABA signaling (Ijaz et al 2017) and this coffee gene was most homologous to Annexin 1 of Arabidopsis, which is a calcium transporter gene known to be induced by water deficits and high temperatures (Huh et al 2010;Liao et al 2017). The two other annexin DEGs (Cc07_g15280 and Cc11_g05800) exhibited only slight transcript increases.…”
Section: Discussionmentioning
confidence: 99%
“…An annexin with a high T = 0 expression showed a strong transcript level rise at the higher water deficit (Cc10_g07300, FC = 2.5). Annexins have been linked to drought and oxidative responses, potentially via ABA signaling (Ijaz et al 2017) and this coffee gene was most homologous to Annexin 1 of Arabidopsis, which is a calcium transporter gene known to be induced by water deficits and high temperatures (Huh et al 2010;Liao et al 2017). The two other annexin DEGs (Cc07_g15280 and Cc11_g05800) exhibited only slight transcript increases.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that only 65% of HS‐upregulated genes were regulated by the HSFA1s suggested that additional transcription factors regulate gene expression in response to HS (Liu et al ). Although studies have revealed a number of transcription factors the expression levels of which in vivo are correlated with the thermotolerance of plants (Davletova et al ; Li et al ; Hsieh et al ; Wang et al ; Guan et al ; Lee et al ; Chao et al ; Liao et al ), it is not clear whether these transcription factors are directly regulated by the HS signaling pathway, or merely the targets of unknown primary transcription factors. Of these transcription factors, the activity of a NAC transcription factor, NAC019, during HS is regulated by protein dephosphorylation (Guan et al ).…”
Section: Heat Shock Signaling Mechanismsmentioning
confidence: 99%
“…Accumulating evidence suggests that ROS actively can interact with Ca 2+ signaling to regulate plant development and various stress responses. In one experiment, the application of exogenous H 2 O 2 induced a sharp increase in intracellular Ca 2+ within 60 s (Liao et al ). Similarly, the addition of a Ca 2+ ionophore, ionomycin, induces a transient increase in ROS production within 60 s (Kimura et al ); however, there is insufficient evidence to determine whether Ca 2+ functions upstream of ROS in transducing the primary HS signal, or vice versa .…”
Section: Heat Shock Signaling Mechanismsmentioning
confidence: 99%
“…The variable N-terminal region interacts with other proteins and is responsible for the functional diversity of ANN 4 .Recent studies have identified the ANN gene family in Arabidopsis thaliana (8 genes), Brassica rapa (13), Solanum lycopersicum (9), Solanum tuberosum (9), Oryza sativa (10), Triticum aestivum (25), Gossypium raimondii (14), Arachis hypogaea L. (8), Hordeum vulgare (11), Medicago truncatula (10), Populus trichocarpa (12), Vitis vinifera (14), Carica papaya (12), Glycine max (22), Cochliobolus sativus (11), Sorghum bicolor (10), Zea mays (12), Brachypodium distachyon (11), Selaginella mollendorffii (5), and Physcomitrella patens (7) via genome-wide analysis 2,5-11 .Studies have shown that ANN gene family plays a significant role in plant development and plant protection during both abiotic and biotic stresses 1,3,12,13 . In Arabidopsis, two ANN genes (AtANN1 and AtANN4) were regulated by abiotic stress, negatively regulated plant tolerance to drought, salinity, and heat stress, while AtANN8 was open Scientific RepoRtS | (2020) 10:4295 | https://doi.org/10.1038/s41598-020-59953-w www.nature.com/scientificreports www.nature.com/scientificreports/ positive regulated the plant abiotic tolerance [14][15][16][17][18][19][20][21] . Studies also demonstrated that AtANN1 and AtANN2 regulated root growth and development [20][21][22] .…”
mentioning
confidence: 99%
“…Studies have shown that ANN gene family plays a significant role in plant development and plant protection during both abiotic and biotic stresses 1,3,12,13 . In Arabidopsis, two ANN genes (AtANN1 and AtANN4) were regulated by abiotic stress, negatively regulated plant tolerance to drought, salinity, and heat stress, while AtANN8 was open Scientific RepoRtS | (2020) 10:4295 | https://doi.org/10.1038/s41598-020-59953-w www.nature.com/scientificreports www.nature.com/scientificreports/ positive regulated the plant abiotic tolerance [14][15][16][17][18][19][20][21] . Studies also demonstrated that AtANN1 and AtANN2 regulated root growth and development [20][21][22] .…”
mentioning
confidence: 99%